PENGARUH LATIHAN MENGGUNAKAN BEBAN KARET TERHADAP PENINGKATAN KECEPATAN TENDANGAN SABIT PENCAK SILAT - Murad, Mukhlis Siratul; Purnomo, Edi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
ABSTRACTThe development of various models and methods of pencak silat training can provide opportunities for athletes to improve their ability especially in increasing the speed of their sickle kick. There are still many pencak silat fighters do their sickle kick slowly, so that it is easily caught by their opponents and it can be a risk for those who have slow sickle kick of being dropped by their opponent. The purpose of this study was to determine the effect of training using rubber load in increasing the speed of pencak silat sickle kick, and how significant the improvement in every training given. This study used a pre-experimental method in the form of one group pre-test and post-test design. In this study, the number of research samples was taken from the total population with 15 pencaksilat fighters as the participants from North Kancil PencakSilat Institution, Ampera, Pontianak. The data collection in this study used a test instrument which was the speed of the sickle kick. The data analysis was with the analysis system used t-test. Based on the results of the data analysis, it was obtained that the t-test was 8.6 and the t-table was 2.14, so t-test > t-table. Accordingly, Ho was declared rejected and Ha was accepted, meaning that there is an influence from rubber load training to increase the speed of the pencaksilat sickle kick. This is proven by the calculations as the results of the research that showed an increase in the speed of pencaksilat sickle kick by 10.55%.Keywords: Rubber Load, Speed, PencakSilat